Mechanisation in dryland agriculture: present status and future needs - K. V.Subrahmanyam; K. Nagasree (Journal of Agricultural Extension Management, 2025)
Nearly 67 per cent of India's total cultivated area of around 142 million hectares is under rainfed agriculture. This area accounts for 44 per cent of total food production. Important food crops like nutritious cereals (91 %), pulses (91 %), oilseeds (80%) and commercial crops like cotton (65%) are cultivated. Dryland agriculture also supports 40 per cent of human population and 60 of the total livestock